3-D gel culture and time-lapse video microscopy of the human vestibular nerve. (December 2014) - Edin, Fredrik; Liu, Wei; Li, Hao; Atturo, Francesca; Magnusson, Peetra U.; Rask-Andersen, Helge
Abstract Conclusions: Human inner ear neurons have an innate regenerative capacity and can be cultured in vitro in a 3-D gel. The culture technique is valuable for experimental investigations of human inner ear neuron signaling and regeneration. Objectives: To establish a new in vitro model to study human inner ear nerve signaling and regeneration. Methods: Human superior vestibular ganglion (SVG) was harvested during translabyrinthine surgery for removal of vestibular schwannoma. After dissection tissue explants were embedded and cultured in a laminin-based 3-D matrix (Matrigel™). 3-D growth cone (GC) expansion was analyzed using time-lapse video microscopy (TLVM). Neural marker expression was appraised using immunocytochemistry with fluorescence and laser confocal microscopy. Results: Tissue explants from adult human SVG could be cultured in 3-D in a gel, indicating an innate potential for regeneration. Cultured GCs were found to expand dynamically in the gel. Growth cone expansion and axonal Schwann cell alignment were documented using TLVM. Neurons were identified morphologically and through immunohistochemical staining.